Bibliometric Analysis of Green Accounting (Sustainable Development Insights, 2026)
This study aims to examine the development, intellectual structure, and emerging trends in green accounting research through a bibliometric approach. Data were collected from a reputable scientific database and analyzed using VOSviewer to map co-occurrence of keywords, thematic clusters, and research evolution over time. The findings show that green accounting has developed into a multidisciplinary field closely linked with sustainability, sustainable development, and climate change. The literature is dominated by measurement-oriented themes such as carbon emissions, carbon footprint, and life cycle assessment, indicating a strong focus on quantifying environmental impact. In addition, the integration of energy efficiency and investment-related topics highlights the role of green accounting in supporting organizational decision-making. However, the analysis also reveals that social and human dimensions remain relatively underexplored.
Keywords: Green Accounting; Sustainability; Sustainable Development; Carbon Emissions; Climate Change; Bibliometric Analysis